The impact of supervisory styles on satisfaction of undergraduate counselling interns in Malaysia / Nur Hafizah Mohd Ali ... [et al.] - Mohd Ali, Nur Hafizah; Hassan, Siti Aishah; Jailani, Othman; Zaremohzzabieh, Zeinab; Lee, Zhi Jie (Universiti Teknologi MARA, 2020)
Clinical experience in counsellor education would not be possible without the kind support of our site supervisors. Day-to-day guidance, advice, and real understanding given to undergraduate students are essential in helping students develop and grow into competent counsellors during their internships. Supervisors play different roles and styles during the supervision process. Thus, this study aimed to assess student perceptions of counsellors' supervisory styles and examine what impact those styles have on the satisfaction of undergraduate counselling interns. This study is quantitative, where a total of 138 counselling interns were selected from four public universities in Malaysia. The results showed that in the Malaysian backdrop, four supervisory styles have a major relationship with supervisory satisfaction, and they are as follows: directive teacher, supportive teacher, counsellor, and delegating colleague (consultant) styles respectively. This study has also filled the knowledge gap existing in the realm of counselling supervisory styles. Furthermore, the newly modified instruments of supervisory styles inventory may be applied to the undergraduate level interns. In practice, this helps supervisors to enhance the supervision process. The undergraduate counselling interns mostly are satisfied with supportive supervisory style. In this regard, supervisors or counsellor educators may find the most functional and appropriate style that suits their interns.